2015
DOI: 10.2147/cia.s74439
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in caregivers of patients with dementia: demographic variables and burden

Abstract: ObjectiveIndividuals suffering from dementia are affected by a progressive and significant global deterioration and, consequently, might require longer assistance in the advanced stage of the illness. The illness is a great burden on the person who takes care of a patient, namely, the caregiver. This study aims to analyze the presence and relationship of specific sociodemographic variables, subjective burden, and depressive symptoms among caregivers of patients with dementia.MethodsThe participants of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
2
52
0
4
Order By: Relevance
“…Caregiving was reported to cause social isolation, anger, irritability, fatigue, and suicidal ideation. Prior studies have also shown a high risk of depressive symptoms [20] and social isolation [21,22] in caregivers of PWD. Notably, participants in the present study did not identify any positive aspects of caregiving such as companionship, self-esteem, personal growth, or the satisfaction of helping others, which have been reported in the literature [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregiving was reported to cause social isolation, anger, irritability, fatigue, and suicidal ideation. Prior studies have also shown a high risk of depressive symptoms [20] and social isolation [21,22] in caregivers of PWD. Notably, participants in the present study did not identify any positive aspects of caregiving such as companionship, self-esteem, personal growth, or the satisfaction of helping others, which have been reported in the literature [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Since we did not ask specifically about positive aspects of care giving, this could partially represent ascertainment bias. However, it also likely reflects high levels of caregiver stress in our population, which had high levels of caregiver burden risk factors including depression, social isolation, low socio-economic status, and lack of choice in being a caregiver [20,21]. In other settings, caregiver support groups have proved to be effective in enhancing caregiver quality of life [25], and should be included as part of any future interventions to improve dementia care in local communities [26].…”
Section: Discussionmentioning
confidence: 99%
“…Outros autores também relatam a feminização do cuidado. Na Itália, em um estudo de corte transversal com 150 cuidadores de idosos, os resultados apresentaram um perfil de cuidadores predominantemente do sexo feminino (78%), idade > d e 50 anos (56%), estado conjugal casado (86%) e escolaridade: ensino fundamental a médio (42%) (FAZIO et al, 2015).…”
Section: Resultsunclassified
“…Furthermore, current research suggests dementia caregivers often suffer from anxiety, depression and physical ills [9][10][11]. Research also indicates that those providing informal care for persons stricken with dementia related disorders many times, offspring are also prone toward mental anguish, depression and even suicidal ideations [12][13][14].…”
Section: Introductionmentioning
confidence: 99%